Refining medical clearance protocol for patients with primary psychiatric complaints in the emergency department - Casey, Christopher Austin; Guzman, Jaime; Salard, Mckailey; Wu, Natalie; Rieger, Ross; Mangham, Payton; Patterson, James (Frontiers in Psychiatry, 2023)
A retrospective review was conducted to evaluate the continued need for labs of psychiatric patients and help identify high risk groups that may need additional intervention prior to medical clearance. Charts of 163 patients from Ochsner LSU Shreveport Psychiatric Crisis Unit (PCU) were reviewed with data collected of history, physical examination, vitals and lab work. Review identified 82 patients (50.3%) that received interventions prior to medical clearance. Most common intervention was intravenous (IV) fluids (n=59; 45%) followed by admission to other service (n=15; 8.4%), imaging (n=10; 7.6%), antihypertensive medication (n=3; 3.1%), cardiac workup (n=3; 2.3%), antibiotics (n=3; 2.3%), lorazepam for undocumented reasons (n=2; 1.5%). Additional interventions completed once included immunizations, antiseizure medication, pain medication, and additional lab work. Causes for IV fluids were reviewed with elevated creatine kinase (CK) (n=31; 50.8%) being most common. Additional causes included undocumented (n=12; 19.7%), tachycardia (n=6; 9.8%), elevated EtOH level (n=3; 4.9%), dehydration (n=2; 3.3%), acute kidney injury (AKI) (n=2; 3.3%), leukocytosis following a seizure (n=1; 1.6%), elevated CK and leukocytosis (n=1; 1.6%), and AKI and elevated CK (n=1; 1.6%). Most common cause for medical admission was elevated CK being cited in 8 out of 15 admissions (53.3%). Additional causes for admission included AKI (n=2; 14.3%), seizures and leukocytosis (n=1; 6.7%), rule out of acute coronary syndrome (ACS) (n=1; 6.7%), alcohol withdrawal (n=1; 6.7%), encephalopathy with drop in hemoglobin and white blood cell count (n=1; 6.7%), and encephalopathy with elevated CK (n=1; 6.7%). Our results support the recommended guidelines set by AAEP for laboratory testing in addition to history, vital signs and physical examination prior to medical clearance. Certain laboratory testing such as CK and CMP were identified to have higher utility for medical intervention while other lab work such as UA and UDS had less of an impact. Further, we suggest that specifically a CK and CMP be obtained on patients presenting with any of the following: agitation, abnormal vital signs, intoxication, or a history of or current stimulant use as these were factors correlated with lab abnormalities that led to interventions.